Cyclooxygenase-2 Inhibitors. 1,5-Diarylpyrrol-3-acetic Esters with Enhanced Inhibitory Activity toward Cyclooxygenase-2 and Improved Cyclooxygenase-2/Cyclooxygenase-1 Selectivity - Biava, Mariangela; Porretta, Giulio Cesare; Poce, Giovanna; Supino, Sibilla; Forli, Stefano; Rovini, Michele; Cappelli, Andrea; Manetti, Fabrizio; Botta, Maurizio; Sautebin, Lidia; Rossi, Antonietta; Pergola, Carlo; et al. (Journal of medicinal chemistry, 2007)
The important role of cyclooxygenase-2 (COX-2) in the pathogenesis of inflammation and side effect limitations of current COX-2 inhibitor drugs illustrates a need for the design of new compounds based on alternative structural templates. We previously reported a set of substituted 1,5-diarylpyrrole derivatives, along with their inhibitory activity toward COX enzymes. Several compounds proved to be highly selective COX-2 inhibitors and their affinity data were rationalized through docking simulations. In this paper, we describe the synthesis of new 1,5-diarylpyrrole derivatives that were assayed for their in vitro inhibitory effects toward COX isozymes. Among them, the ethyl-2-methyl−5-[4-(methylsulfonyl)phenyl]-1-[3-fluorophenyl]-1H-pyrrol-3-acetate (1d), which was the most potent and COX-2 selective compound, also showed a very interesting in vivo anti-inflammatory and analgesic activity, laying the foundations for developing new lead compounds that could be effective agents in the armamentarium for the management of inflammation and pain.